Conversations - Mats Köster; Paul Voss (Center for Economic Studies and ifo Institute (CESifo), 2023)
We develop a theory of conversations. Two agents with different interests take turns choosing the topic of the conversation. Talking about a single topic allows them to delve deeper, making the conversation more informative (or enjoyable). To capture this dynamic, we assume that the marginal utility from conversing increases when the agents stay on topic. The equilibrium conversation is extreme: it either maximizes or minimizes welfare. Long conversations are deep and thus efficient. Short ones are often superficial. The topic of a deep conversation depends in subtle ways on who speaks when. Applications range from echo chambers to team production.
Keywords: D83; 330; communication; information acquisition; team production